ORGANIZATION OF ANTI-EPIDEMIC MEASURES DURING THE ANTHRAX OUTBREAK IN THE YAMALO-NENETS AUTONOMOUS DISTRICT IN 2016 - Yu. V. Demina; L. A. Nechepurenko; S. A. Poznakhareva; Ya. E. Pashina; A. G. Ryazanova; L. Yu. Aksenova; O. V. Maletskaya; E. B. Zhilchenko; V. V. Khar´kov; L. E. Kosareva; G. V. Erdni-Goryaeva; Ю. В. Демина; et al. (Problems of Particularly Dangerous Infections, 2017)
The organizational peculiarities of anti-epidemic measures during the anthrax outbreak in the Yamalo-Nenets Autonomous District in 2016 are presented. Complex of these measures provided for anthrax patients active identification and hospitalization, preventive immunization and emergency antibiotic prophylaxis of risk groups, vaccination of reindeer, utilization of fallen animals. Disinfection, deratization and desinsection measures were performed. Native residents were evacuated from infection focus and sensitization campaign among the population was carried out. Organized were sanitary inspection stations and temporary accommodation points. Due to operational implementation of anti-epidemic measures in the interagency format the anthrax focus was localized within one incubation period. Представлены особенности организации противоэпидемических мероприятий во время вспышки сибирской язвы в Ямало-Ненецком автономном округе в 2016 г. В результате комплекса мер активно выявлены и госпитализированы больные, проведена иммунизация и экстренная антибиотикопрофилактика групп риска заражения, вакцинация северных оленей, утилизация туш павших животных. Осуществлены дезинфекционные, дератизационные и дезинсекционные мероприятия. Организована эвакуация коренных жителей из очага инфекции, проведена разъяснительная работа с населением, развернуты санитарные пропускники и пункты временного размещения. Благодаря оперативно реализованным противоэпидемическим мерам в межведомственном формате очаг сибирской язвы был локализован в течение одного инкубационного периода.